Pola Hubungan Etnik Cina dengan Masyarakat Pribumi di Bengkalis - Hasbullah Hasbullah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
Cohesion and national integration is a major challenge in the process of nation-state formation. The challenge was complicated because the Indonesian society is pluralistic, whether viewed horizontally or vertically. One of the unresolved issues in relation to the indigenous ethnic Chinese are confounding issues that led to the integration of the nation. The relationship between ethnic Chinese - native Bengkalis is quite good because of the cooperation mutualistis. However, this condition only occurs in sectors of the economy and not involve other parts are quite important in life. In these relationships also create stereotypes as a continuation of the colonial legacy that has placed the ethnic Chinese as the middle class. This led to jealousy of the indigenous groups mainly derived from economic inequality. This is a potential that can cause conflict if not handled seriously and carefully by various parties, especially in the era of reform, democracy and transparency.